1996
DOI: 10.1103/physrevlett.77.5365
|View full text |Cite
|
Sign up to set email alerts
|

Light Induced Single Molecule Frequency Shift

Abstract: A light induced frequency shift of the 0-0 line was measured in two-photon excitation spectra of single diphenyloctatetraene molecules doped in a crystal matrix. The shifts were proportional to the laser power with a slope of about 600 MHz͞W when the laser beam of about 300 mW power was focused to a diameter of 2 mm. Significantly, the observed line broadenings were an order of magnitude smaller than the shifts. The effect is ascribed mainly to a "fast" energy exchange between a local vibration and thermal pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Thus, the linewidth is 26-28 MHz on a short time scale, in agreement with OPE data. OPE spectra do not show spectral dynamics in the time range 10 23 10 2 s. This confirms that the difference between the SM linewidths in OPE and TPE spectra is caused by SD induced by the strong illumination at 888 nm, a hypothesis discussed in [22,23]. The dependence of the SD on the IR power was not studied in this work.…”
Section: Physical Chemistry Laboratory Swiss Federal Institute Of Tesupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, the linewidth is 26-28 MHz on a short time scale, in agreement with OPE data. OPE spectra do not show spectral dynamics in the time range 10 23 10 2 s. This confirms that the difference between the SM linewidths in OPE and TPE spectra is caused by SD induced by the strong illumination at 888 nm, a hypothesis discussed in [22,23]. The dependence of the SD on the IR power was not studied in this work.…”
Section: Physical Chemistry Laboratory Swiss Federal Institute Of Tesupporting
confidence: 71%
“…This technique, which we call intensity-time-frequency correlation (ITFC) SM spectroscopy, can yield microsecond or even better time resolution with an intrinsic theoretical limit at the luminescence lifetime. The ITFC technique is used for studying dynamics in two-photon excitation (TPE) spectra of DPOT molecules in an n-tetradecane matrix [21], where a significant difference between the linewidths in one-photon excitation (OPE) and TPE spectra was observed and tentatively explained by SD induced by the powerful laser illumination required for TPE [22,23]. This explanation agrees with the significant line broadening observed for OPE data in the presence of infrared illumination [24].…”
supporting
confidence: 62%
“…[25][26][27][28][29] The combination of one-and two-photon excitation studies has shown that the right choice of a guest-host system is crucial in singlemolecule spectroscopy because the electronic excited-state properties depend sensitively on the host species. For instance, the replacement of the host molecule by its predeuterated form may lead to significant changes in the single molecule spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of such methods can be fulfilled in a nano diagnostics of complex polymer structures, and track membranes also. Moreover, the photophysical (spectral) characteristics of such probes are very sensitive to local environment, that can be used in future for characterization of that environment [2][3][4][5][6][7].Determination of all three spatial coordinates with nanometer precision is possible due to use of an idea of instrumental transformation of point spread function in double helix scheme using adaptive optics' phase transformation elements [8].The purpose of introduced work is development of methods of 3D laser spectromicroscopy of single colloid nanocrystals (quantum dots, QD) for nanodiagnostics of track etched membranes. …”
mentioning
confidence: 99%
“…The potential of such methods can be fulfilled in a nano diagnostics of complex polymer structures, and track membranes also. Moreover, the photophysical (spectral) characteristics of such probes are very sensitive to local environment, that can be used in future for characterization of that environment [2][3][4][5][6][7].…”
mentioning
confidence: 99%